1996
DOI: 10.1111/j.1365-2516.1996.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in factor VIII inhibitor reactivity with different commercial factor VIII preparations

Abstract: During treatment of a haemophilia A patient with a high-responding inhibitor against factor VIII coagulant activity (VIII:C), we observed a difference in recovery of VIII:C depending upon which factor concentrate was infused. Inhibitor plasma samples or IgG fraction from seven patients were tested against a panel of seven different commercially available factor VIII concentrates of which five were plasma-derived and two recombinant. In two of the plasma samples, inhibitor titres manifested a wide range of valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 19 publications
6
75
0
Order By: Relevance
“…Cumulative evidence stemming from national and international registries [5][6][7][8][9] identified the following as potential prognostic factors for a positive response: young age at ITI, recent onset of inhibitors, low anamnestic peak titres and low titres at ITI start-up. Recently, case series [22,21] and in vitro studies [16,29] have suggested a potential additional role for FVIII concentrates with a high content of VWF in the induction of immune tolerance. We report, herewith, the results of the first prospective study on ITI using exclusively a high purity VWF/FVIII complex concentrate, involving 17 patients at high risk of poor response treated with different dosages of the study concentrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative evidence stemming from national and international registries [5][6][7][8][9] identified the following as potential prognostic factors for a positive response: young age at ITI, recent onset of inhibitors, low anamnestic peak titres and low titres at ITI start-up. Recently, case series [22,21] and in vitro studies [16,29] have suggested a potential additional role for FVIII concentrates with a high content of VWF in the induction of immune tolerance. We report, herewith, the results of the first prospective study on ITI using exclusively a high purity VWF/FVIII complex concentrate, involving 17 patients at high risk of poor response treated with different dosages of the study concentrate.…”
Section: Discussionmentioning
confidence: 99%
“…VWF, beyond being the physiological FVIII-stabilizing protein [12,13] was shown to protect FVIII from neutralizing antibodies in vitro [14][15][16][17][18][19][20]. Accordingly, a better response to ITI was observed in two case series when ITI carried out with FVIII concentrates rich in VWF [21,22] was compared with ITI carried out with VWF-free FVIII concentrates either plasmaderived monoclonally purified or recombinant.…”
Section: Introductionmentioning
confidence: 99%
“…38 Several clinical observations and in vitro studies suggested that von Willebrand factor in factor VIII concentrates protects factor VIII from circulating inhibitory antibodies by masking antibody epitopes on the C2 domain. 37,39,40 Additionally, hemophilic mice treated with factor VIII products without von Willebrand factor developed higher peak inhibitor titers than those treated with factor VIII products that contained von Willebrand factor. 41 We showed that there is no decreasing trend in inhibitor development with an increasing von Willebrand factor content.…”
Section: Fviii Product Type and Inhibitors Inmentioning
confidence: 99%
“…Based on the previously mentioned in vivo finding on varying recoveries with two different types of FVIII concentrates, we have shown that some plasmas from patients with inhibitors display less reactivity against VWF containing concentrates when compared with highly purified plasma-derived concentrates or recombinant FVIII concentrates [11]. These findings have since been corroborated by others [12,13].…”
Section: In Vitro Observations On Antibody Reactivity With Fviii Concmentioning
confidence: 80%